RESEARCH OF THE RANGE OF HERBAL TEA ON THE UKRAINIAN MARKET - Трішкіна, Ніна; Кучерук, Надія (SWorldJournal, 2026)
The article examines the current state of the herbal tea market in Ukraine. The main aspects of the Ukrainian herbal tea market are analyzed, namely: dependence on imports, the popularity of herbal blends, market leaders, consumer choice factors. The main